The Relationship among School Mindfulness, Classroom Anxiety, and High School Student Life Satisfaction - Riaz, Husna; Ali, Yumna (Educational Challenges, 2023)
Purpose. The study aims to improve student life throughout the school years by exploring the use of mindfulness-based instruction to reduce classroom anxiety. Many school systems in Asia do not use mindful based instruction at primary, secondary and high school education. Emphasis on academic achievement as measured in terms of grade scoring and competitive exam results is high, and leads to significant stress on students. It is believed that mindfulness coaching could help reduce overall stress levels in high school students. Methodology. The study is a correlational design in which convenience sampling was used. It aims to measure school mindfulness by Hoy (2004), classroom anxiety by Richmond (2001), and high school student life satisfaction by Heubener (1991) for a sample of 80 high school students drawn from the private school system of Pakistan. Results. The study reported moderate to weak positive correlations between the three constructs. It was found that there was a significant link between school mindfulness, student life satisfaction, and classroom anxiety. The study reported that age and gender have no significant impact on school mindfulness, student life satisfaction and classroom anxiety. Conclusions. The study indicates the development of mindfulness-based training at the school level to improve student life satisfaction. The study indicates the possibility of Western mindfulness instruction courses being implemented in the Eastern traditional school system. School mindfulness can help students to meaningfully grow in their academic careers. It further can enhance their coping and stress handling techniques as they proceed into higher education. The study will pave way for the implementation of school mindfulness programs and workshops to be delivered by mindfulness certified instructors and counselors, which is at present a rarity in traditional academic system.